Patērētājizglītības būtība pamatskolā - Danilāne, Līga (Latvijas Universitāte, 2014)
Promocijas darba „Patērētājizglītības būtība pamatskolā” mērķis: apzināt patērētājizglītības būtību, pedagoģiskās likumības vispārizglītojošās pamatskolas procesā, izveidot metodoloģisko pamatu patērētājizglītības satura integrēšanai skolas mācību priekšmetu saturā, transformējot mācīšanas procesu skolēna mācīšanās procesā. Pētījumā veikta literatūras un avotu analīze par patērētājizglītības būtību un attīstību Latvijas un Eiropas kultūrvidē, apzināts patērētājizglītības jēdziens un patērētājizglītības konceptuālais ietvars pamatskolas mācību procesā, veikta skolēnu vajadzību izpēte un noteikts Latvijas kultūrapstākļiem atbilstošs patērētājizglītības saturs. Promocijas darbā izveidota patērētājizglītības programma, izstrādāti kritēriji un līmeņi tās aprobācijai praksē, analizēti aprobācijas rezultāti un sagatavoti ieteikumi patērētājizglītības satura ieviešanai pamatizglītības mācību procesā.

The aim of the thesis “The essence of consumer education in primary school” is to study the essence of consumer education, pedagogical regularities in general education primary school process, to create a methodological framework for the integration of consumer education content in school curriculum, transforming teaching process into student's learning process. In the research work there has been done the analysis on the sources and literature concerning the essence of consumer education and its development in Latvian and European cultural environment, the term consumer education and consumer education conceptual framework in basic education process have been studied, students’ needs have been analyzed and consumer education content, which corresponds to Latvian cultural environment, has been determined. In the thesis there has been elaborated a consumer education program, as well as criteria and levels for its approbation in practice have been developed, the results of the approbation have been analyzed and recommendations for the implementation of consumer education content in basic education learning process have been prepared.
The essence of consumer education in primary school
Elektroniskā versija nesatur pielikumus
Keywords: Pedagoģija; Skolas pedagoģija; patērētājizglītība; pamatizglītība; mācību sasniegumi patērētājizglītībā; School education; consumer education; basic education; learning outcomes in consumer education